1977
DOI: 10.1017/s0021859600027167
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Nigerian root and tuber crops: effect of potassium on starch yields, HCN content and nutrient uptake of cassava cultivars (Manihot esculenta)

Abstract: Field experiments were made in the rainforest zone of Western Nigeria over three cropping seasons on the effects of potassium fertilizer of one local cassava cultivar 53101 and two improved cultivars 60506 and 60447 which were F x hybrids of the former. The results showed that K-fertilizer increased the starch yields only slightly. Cultivar 60506 produced significantly higher starch yields (P < 0-01) than the local strain, 53101, while cultivar 60447 gave lower starch recovery than the local cultivar.A definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…Zero and 100 kgK/ha Figure 9 and several reports [70,79,80,[82][83][84][85][86] have shown significant responses to K fertilizer in different soils, particularly when cassava was grown continuously for several years in the same field due to removal of large K amount (>70% of extracted K) in harvested storage roots. Moreover, research at CIAT [79,80,87] have indicated the existence of genetic diversity in response to K application and in K use efficiency, which warranted further selection for tolerance to low-K soils.…”
Section: Performance Of Some Cassava Clones Atmentioning
confidence: 99%
“…Zero and 100 kgK/ha Figure 9 and several reports [70,79,80,[82][83][84][85][86] have shown significant responses to K fertilizer in different soils, particularly when cassava was grown continuously for several years in the same field due to removal of large K amount (>70% of extracted K) in harvested storage roots. Moreover, research at CIAT [79,80,87] have indicated the existence of genetic diversity in response to K application and in K use efficiency, which warranted further selection for tolerance to low-K soils.…”
Section: Performance Of Some Cassava Clones Atmentioning
confidence: 99%
“…No significant response to K was observed in field experiments conducted in Nigeria (Obigbesan, 1977) nor in Ghana (Takyi, 1972). In Madagascar, however, Roche et al (1957) and Cours et al (1961) found that K was the main limiting nutrient, and applications of 110 kg K 2 O ha −1 were recommended (Anon, 1952(Anon, , 1953.…”
Section: Potassiummentioning
confidence: 99%
“…Therefore, extra early cowpea varieties available at llTA should be suitable components of maize-based intercropping systems. Given the low organic matter and low N levels of most West African soils (OBIGBESAN 1977, KANG et al 1981 and high N requirements of maize, much N could be saved if part of the 64-131 kg ha"' N (KANG et al 1981) or about 157 kg N ha"' (AGBOOLA andFAYEMI 1972) fixed by cowpea were available to the associtated maize.…”
Section: Introductionmentioning
confidence: 99%